Pengaruh Problem Based Learning dengan Pendekatan Culturally Responsive Teaching terhadap Kemampuan Literasi Matematis Siswa pada Materi Statistika - Anggraini, Baiq Aprilia Noor; Purwosetiyono, FX. Didik; Sumarti, Sumarti; Purwati, Heni (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2024)
Ambarwati, D., & Kurniasih, M. D. (2021). Pengaruh Problem Based Learning Berbantuan Media Youtube Terhadap Kemampuan Literasi Numerasi Siswa. Jurnal Cendekia : Jurnal Pendidikan Matematika, 5(3), 2857–2868. https://doi.org/10.31004/cendekia.v5i3.829 Ardianti, R., Sujarwanto, E., & Surahman, E. (2022). Problem-based Learning: Apa dan Bagaimana. Diffraction, 3(1), 27–35. https://doi.org/10.37058/diffraction.v3i1.4416 Crosswhite, F. J., Dossey, J. A., & Frye, S. M. (1989). NCTM Standards for School Mathematics: Visions for Implementation. Journal for Research in Mathematics Education, 20(5), 513–522. Depdiknas. (2006). Permendiknas No 22 Tahun 2006 Tentang Standar Isi. Jakarta: Depdiknas. Erria, R., Buyung, B., Nirawati, R., & Paruntu, P. E. (2023). Pengaruh Problem Based Learning Terhadap Literasi Matematika. Journal of Educational Review and Research, 6(1), 78. https://doi.org/10.26737/jerr.v6i1.4690 Farida, R. N., Qohar, A., & Rahardjo, S. (2021). Analisis Kemampuan Literasi Matematis Siswa SMA Kelas X Dalam Menyelesaikan Soal Tipe Pisa Konten Change and Relationship. Jurnal Cendekia : Jurnal Pendidikan Matematika, 5(3), 2802–2815. https://doi.org/10.31004/cendekia.v5i3.972 Gay, G. (2000). Culturally Responsive Teaching: Theory, Research, and Practice. New York: Teachers College Press. Teachers College Press. Hwang, J., & Ham, Y. (2021). Relationship between mathematical literacy and opportunity to learn with different types of mathematical tasks. Journal on Mathematics Education, 12(2), 199–222. https://doi.org/10.22342/JME.12.2.13625.199-222 Lechner, C. M., Gauly, B., Miyamoto, A., & Wicht, A. (2021). Stability and change in adults’ literacy and numeracy skills: Evidence from two large-scale panel studies. Personality and Individual Differences, 180(May), 110990. https://doi.org/10.1016/j.paid.2021.110990 Masliah, L., Nirmala, S. D., & Sugilar, S. (2023). Keefektifan Model Pembelajaran Problem Based Learning ( PBL ) terhadap Kemampuan Literasi dan Numerasi Peserta Didik di Sekolah Dasar. Jurnal Basicedu, 7(1), 1–10. https://doi.org/10.31004/basicedu.v7i1.4106 Maulana, G., Zaenuri, & Junaedi, I. (2020). Pattern of Problem Solving Skill Reviewed Based on Student Cognitive Style After Experienced Problem Based Learning Model with Ethnomathematics Nuances. Journal of Primary Education, 9(2), 209–2019. https://journal.unnes.ac.id/sju/index.php/jpe Maulana, & Mediatati, N. (2023). Penerapan Model Project Based Learning Melalui Pendekatan Culturally Responsive Teaching Untuk Meningkatkan Kolaborasi dan Hasil Belajar Siswa. Literasi: Jurnal Ilmu Pendidikan, 15(3), 153–163. www.ejournal.almaata.ac.id/literasi Nur Aisah, D., Munandar, K., Wadiono, G., & Ridlotul Jannah, S. (2023). Increasing Students’ Creative Thinking Through Differentiated Learning with an CRT-Integrated PjBL Model Bioeduca: Journal of Biology Education Increasing Students’ Creative Thinking Through Differentiated Learning with an CRT-Integrated PjBL Model. Bioeduca: Journal of Biology Education, 5(2), 125–132. http://journal.walisongo.ac.id/index.php/bioeduca OECD. (2019). PISA 2018 Assessment and Analytical Framework. In OECD Publishing. OECD. (2023a). Equity in education in PISA 2022. In PISA 2022 Results (Volume I): The State of Learning and Equity in education (Vol. 1). https://www.oecd-ilibrary.org/education/pisa-2022-results-volume-i_03c74bdd-en OECD. (2023b). PISA 2022 Results (Volume II): Learning During – and From – Disruption. In OECD Publishing: Vol. II. https://www.oecd-ilibrary.org/education/pisa-2022-results-volume-ii_a97db61c-en Porter, P. D. (2021). Using culturally responsive teaching and data-driven instruction in mathematics to create equity and equality: Culturally responsive mathematics. Research Anthology on Culturally Responsive Teaching and Learning, 793–817. https://doi.org/10.4018/978-1-7998-9026-3.ch043 Safirah, A. D., Ningsih, Y. F., Suhartiningsih, S., Masyhud, M. S., & Hutama, F. S. (2024). Model Problem Based Learning dengan Pendekatan Culturally Responsive Teaching terhadap Keterampilan Berpikir Kritis Siswa SD. Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan Dan Hasil Penelitian, 10(2), 87–96. https://doi.org/10.26740/jrpd.v10n2.p87-96 Sari, A., Sari, Y. A., & Namira, D. (2023). Penerapan Model Pembelajaran Problem Based Learning Terintegrasi Culturally Responsive Teaching (Crt) Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas X Ipa 2 Sma Negeri 7 Mataram Pada Mata Pelajaran Kimia Tahun Ajaran 2022/2023. Jurnal Asimilasi Pendidikan, 1(2), 110–118. https://doi.org/10.61924/jasmin.v1i2.18 Taher, T. (2023). Analisis Keterampilan Komunikasi dan Kolaborasi Siswa Introvert dengan Pendekatan Culturally Responsive Teaching. Jambura Journal of Educational Chemistry, 5(1), 21–27. https://doi.org/10.34312/jjec.v5i1.17463 Wati, L. K., & Suendarti, M. (2020). Pengaruh Metakognisi dan Disposisi Matematik terhadap Literasi Matematika (Survei pada SMA Negeri di Kota Tangerang). Jurnal Pendidikan MIPA, 3(3), 1–13. Zuliyanti, I., Purwosetiyono, F. X. D., Wibawa, A., & Ariyanto, L. (2024). Efektivitas Model PBL berbantuan LKPD terhadap Kemampuan Literasi Matematika Peserta Didik pada Materi Peluang. 4, 198–205.